Liberdade, autenticidade e engajamento: pressupostos de ontologia moral em Sartre - Hilgert, Luiza Helena (2011)
Think ethics is not the same as conjecture rules, regulations, prescribed values, established standards and stereotyped behaviors. At least it's not that the description of the human condition conceived by the French philosopher Jean-Paul Sartre, through his phenomenological ontology allows support. The ontological ethics is not limited to dogmatic and regulatory fields, Sartre operates a deconstruction of the metaphysical foundations: remove models, fixed behaviors, prototypes, archetypes, gods, concomitantly, transcends all attempts to assert the good and evil with based on an substrate absolute extreme, like the nature or essence. The moral ontology we describe here, using mainly the works of Sartre's period - so called metaphysical, has the freedom as its foundation and its greatest value, is therefore a theory of ambiguity, like the human condition. It must be understood freedom in this sense, not as a mere human attribute, but on the ontological way, as a fundamental structure of man. To found the values, actions and choices consistently with the human condition, the traditional moral laws based on rational or universal rules should be suspected. The ontological ethics that we want to bring up is like a large building whose foundation is the notion of freedom and built on it are the conceptions of man and world. The main work in which such building may be appreciated, and justify under which our research was published in 1943, entitled Being and Nothingness, it found a detailed and thorough analysis of the human condition, allowing a find out a kind of ethics consistent with the human reality in the situation. The notion of freedom in Sartre's phenomenological analysis, it is not, however, the only aspect of ethics, it comes with responsibility, authenticity, engagement and relationship with others.